Pengaruh Current Ratio, dan Return On Equity, terhadap Harga Saham Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (Studi Kasus Pada Perusahaan Sub Sektor Transportasi Di Masa Pandemi Covid-19) - Annisa Rahma Ilahi; Dessi Susanti (Jurnal Salingka Nagari, 2023)
The purpose of this study is to examine the impact of liquidity ratio, return on equity, on stock prices of companies listed in the transport sub-sector of the Indonesian Stock Exchange from Q1 2020 to Q3 2021. The study lists companies in the transport sub-sector listed on the Indonesian Stock Exchange, with a total of 37 companies listed for the third quarter of 2020-2021. The sampling technique used was targeted sampling. The information used is secondary information extracted from the documentation methods. Method used is multiple regression analysis. Based on our findings, we know that the return of the stock variable partially negatively impacts the stock variable with a significant value of 0.002<0>0.05, and increased sales volume has no impact on price. The meaningful part 0.657 > 0.05. The influence of the independent variable on the dependent variable is 10.7%.